REVITALISASI NILAI-NILAI PENDIDIKAN AKHLAK DALAM MENYIKAPI BULLYING DI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Sulton Alamsyah, Akhmad; Indra Setiabudi, Dede; Humaeroh, iis (Sindoro: Cendikia Pendidikan, 2024)
Moral education in Islam plays a crucial role in shaping the character and culture of society. In the context of globalization, the development of moral values through positive habits becomes a priority to create a generation with strong character. This study examines the strategies employed by teachers to revitalize moral education values in addressing bullying at Madrasah Ibtidaiyah Ma’had Al-Zaytun. A qualitative approach with a field research method was used. The research data includes both primary and secondary sources, collected through observation, interviews, and documentation with a population of teachers and 209 fifth-grade students. The validity of the data was tested using triangulation techniques. Data analysis was conducted through data reduction, data presentation, data verification, and conclusion drawing. The results indicate that effective strategies include prioritizing moral education, active teacher involvement in addressing bullying, supervision and guidance, collaboration with school management, integrative teaching methods, as well as strict reporting and control systems. The moral values implemented encompass the development of independent character, behavior control, the teaching of moral values, and handling of special cases. The implementation of these values has proven successful in creating a safe and conducive learning environment, as well as fostering students with noble character. This study emphasizes the importance of a holistic and collaborative approach to moral education in combating bullying and shaping a generation with strong character. Full support from all school elements, including teachers and management, is essential in creating an environment that effectively nurtures moral development and student character formation. Keywords: Revitalization, Moral Education, Bullying